In defense of self and others-- issues, facts & fallacies: the realities of the law enforcement's use of deadly force - Patrick, Urey W. (Carolina Academic Press)
The law - A brief survey of history & procedures -- Federal constitutional standards -- The use of deadly force -- Wound ballistics -- Training vs qualification -- Physiological imperatives -- Tactical factors & misconceptions -- Suicide by cop & the mentally ill subject-- Risk & responsibility -- Aftermath & impact -- Deadly force policy- -- Case histories